2011
DOI: 10.1007/s10800-011-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

Bench-scale electrochemical system for generation of CO and syn-gas

Abstract: A flow cell based, bench-scale electrochemical system for generation of synthesis-gas (syn-gas) is reported. Sensitivity to operating conditions such as CO 2 flow, current density, and elevated temperature are described. By increasing the temperature of the cell the kinetic overpotential for the reduction of CO 2 was lowered with the cathode voltage at 70 mA cm -2 decreased by 0.32 V and the overall cell voltage dropping by 1.57 V. This equates to an 18% increase in cell efficiency. By closely monitoring the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 22 publications
9
159
1
Order By: Relevance
“…Reliable information on the CO 2 RR and OER reaction kinetics specifically for gas diffusion configurations are, however, rare in literature. [27][28][29] For the sake of simplicity we therefore estimate CO 2 RR and OER overpotentials from experimental data available for polycrystalline catalyst materials in aqueous reaction environments. For such considerations we assume that the particular catalyst performance does not alter when going from an Ta ble 2.…”
Section: Energy Efficiency Of Co 2 Electrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable information on the CO 2 RR and OER reaction kinetics specifically for gas diffusion configurations are, however, rare in literature. [27][28][29] For the sake of simplicity we therefore estimate CO 2 RR and OER overpotentials from experimental data available for polycrystalline catalyst materials in aqueous reaction environments. For such considerations we assume that the particular catalyst performance does not alter when going from an Ta ble 2.…”
Section: Energy Efficiency Of Co 2 Electrolysismentioning
confidence: 99%
“…1C. Importantly, the CO/H 2 ratio can be readily tuned by changing cell voltage [27,29] and potentially by the right choice of the catalyst system. are used.…”
Section: Gdementioning
confidence: 99%
“…[12] With respect to conversion, most studies that focus on the electroreduction of CO 2 to CO report current densities in the range of 2-118 mA cm À2 under ambient conditions, and most of these studies use Ag as the cathode catalyst. [7] For example, Dufek et al [13] and Delacourt et al [14] reported partial current densities for CO (j CO ) of less than 60 mA cm À2 at À1. while the Ag loading was decreased by a factor of 20.…”
Section: à2mentioning
confidence: 99%
“…K 2 SO 4 (0.5 m), a widely used electrolyte in CO 2 reduction studies, [13] was used here. In a standard three-electrode cell, KOH would react with CO 2 to form carbonate/bicarbonate, which would, therefore, decrease the electrolyte pH significantly (from 13.58 to 9.96) and thus the amount of the active species, molecular CO 2 .…”
Section: Ag Particle Size and Size Distributionmentioning
confidence: 99%
“…[ 21 , 30 , 31 ] The electrically driven (nonsolar) electrolysis of dissolved carbon dioxide is under investigation at or near room temperature in aqueous, non-aqueous, and PEM media. [32][33][34][35][36][37][38][39][40][41] These are constrained by the thermodynamic and kinetic challenges associated with ambient temperature, endothermic processes, of a high electrolysis potential, large overpotential, low rate and low electrolysis effi ciency. High-temperature, solid-oxide electrolysis of carbon dioxide dates back to suggestions from the 1960s to use such cells to renew air for a space habitat, [42][43][44] and the sustainable rate of the solid oxide reduction of carbon dioxide is improving rapidly.…”
Section: Introductionmentioning
confidence: 99%